2021
DOI: 10.1021/acsami.1c11872
|View full text |Cite
|
Sign up to set email alerts
|

Ti2O3 Nanoparticles with Ti3+ Sites toward Efficient NH3 Electrosynthesis under Ambient Conditions

Abstract: Electrocatalytic nitrogen reduction reaction (NRR) enabled by introducing Ti 3+ defect sites into TiO 2 through a doping strategy has recently attracted widespread attention. However, the amount of Ti 3+ ions is limited due to the low concentration of dopants. Herein, we propose Ti 2 O 3 nanoparticles as a pure Ti 3+ system that performs efficiently toward NH 3 electrosynthesis under ambient conditions. This work has suggested that Ti 3+ ions, as the main catalytically active sites, significantly increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Compared to the industrial Haber–Bosch process, using catalysts and renewable electricity to drive electrochemical nitrogen fixation provides a new strategy for ammonia production under ambient conditions. 150–152 There are two common parameters used to evaluate whether the catalysts are efficient or have higher activity, namely faradaic efficiency (FE) and NH 3 yield rate ( V NH 3 ). Faradaic efficiency reflects the selectivity of products in the ammonia synthesis process.…”
Section: Applications Of Mos2-based Materials In Nrr Activitymentioning
confidence: 99%
“…Compared to the industrial Haber–Bosch process, using catalysts and renewable electricity to drive electrochemical nitrogen fixation provides a new strategy for ammonia production under ambient conditions. 150–152 There are two common parameters used to evaluate whether the catalysts are efficient or have higher activity, namely faradaic efficiency (FE) and NH 3 yield rate ( V NH 3 ). Faradaic efficiency reflects the selectivity of products in the ammonia synthesis process.…”
Section: Applications Of Mos2-based Materials In Nrr Activitymentioning
confidence: 99%
“…23–27 Recently, defect engineered TiO 2 , which is abundant and nontoxic, is established as an efficient catalyst towards NRR and has gained increasing attention in the artificial N 2 fixation process. 28–31 Nonetheless, most of the reported catalysts so far in this category could not deliver a promising yield and FE in acidic conditions. Recently, K 2 Ti 4 O 9 nanobelts, reported by Wu et al , attained 22.88 μg h −1 mg cat −1 yields and 5.87% FE at −0.5 V versus reversible hydrogen electrode in 0.1 M KOH.…”
Section: Introductionmentioning
confidence: 99%
“…Attentions have thus focused on designing and developing earth-abundant alternatives. [18][19][20][21] TiO 2 with non-toxicity, natural abundance, and high chemical stability has been widely used in sensing, 22 energy storage/ conversion, [23][24][25] and catalysis. 26,27 We found that TiO 2 nanosheets array is an active NRR catalyst but suffers from inferior conductivity.…”
mentioning
confidence: 99%